Economic Growth, Inflation, and Regional Minimum Wage: An Empirical Investigation of the Open Unemployment Rate in Sumatera, Indonesia - Rian Putra; Ketut Sukiyono; Purmini Purmini (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2021)
The purpose of this study is to investigate the determinants of the open unemployment rate in Sumatera island – Indonesia. We conjecture that the variation of the open unemployment rate (OUR) is the function of economic growth (EG), inflation (INF), and regional minimum wage (RMW). Using the sample of ten provinces in Sumatera island from 2006 to 2018, we further perform a panel data analysis with a random effect model (REM). The obtained empirical results show that there is a negative association between the independent variables (i.e., EG, RMW) and the dependent variable (OUR), while INF does not show any significant association with OUR. Referring to the empirical evidence, we infer that economic growth and regional minimum wage play an essential role in explaining the variation of the open unemployment rate in Sumatera island..